2008
DOI: 10.1002/jcb.21726
|View full text |Cite
|
Sign up to set email alerts
|

Role and regulation of human XRCC4‐like factor/cernunnos

Abstract: In mammalian cells, non-homologous end joining (NHEJ) is the major double strand break (DSB) repair mechanism during the G(1) phase of the cell cycle. It also contributes to DSB repair during the S and G(2) phases. Ku heterodimer, DNA PKcs, XRCC4 and DNA Ligase IV constitute the core NHEJ machinery, which joins directly ligatable ends. XRCC4-like factor/Cernunnos (XLF/Cer) is a recently discovered interaction partner of XRCC4. Current evidence suggests the following model for the role of XLF/Cer in NHEJ: after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
12
2
Order By: Relevance
“…14 Phosphorylation of DNA-PKcs, either trans-autophosphorylation or by ATM, promotes its dissociation from DNA ends, 20 and enhances access by the Ligase IV/XRCC4/XLF protein complex, which completes the ligation reaction. 21 Defects in classic NHEJ proteins channel DSBs toward alternative NHEJ (Alt-NHEJ), a robust but less accurate pathway that is regulated by PARP1 13 binding to the free DNA ends instead of the Ku complex. This pathway requires single-strand end-resection by the MRE11/RAD50/NBS1 (MRN) complex, 22 and the CtIP tumor-suppressor.…”
Section: Mechanisms Of Dna Repairmentioning
confidence: 99%
“…14 Phosphorylation of DNA-PKcs, either trans-autophosphorylation or by ATM, promotes its dissociation from DNA ends, 20 and enhances access by the Ligase IV/XRCC4/XLF protein complex, which completes the ligation reaction. 21 Defects in classic NHEJ proteins channel DSBs toward alternative NHEJ (Alt-NHEJ), a robust but less accurate pathway that is regulated by PARP1 13 binding to the free DNA ends instead of the Ku complex. This pathway requires single-strand end-resection by the MRE11/RAD50/NBS1 (MRN) complex, 22 and the CtIP tumor-suppressor.…”
Section: Mechanisms Of Dna Repairmentioning
confidence: 99%
“…In contrast, the 3' overhangs are clipped with a preference for leaving a 4-or 5-nuleotide single-stranded overhang (10). After autophosphorylation, DNA-PKcs recruits XRCC4/ligase Ⅳ complex to process the DNA ends and to initiate re-ligation to form a single DNA molecule (5,11,12). Thus, targeted inhibition of DSB repair proteins is an attractive approach in the development of potent radiation therapy strategies (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…19,20 So far, the most important action of XLF seems to be the stimulation of LIG4 activity, 21,22 probably by stabilizing the XRCC4-LIG4 complex on DNA and promotion of DNA strand alignment. 23 However, recently, Lescale et al have shown that the RAG postcleavage complex (RAG-PCC) and XLF have overlapping functions and have suggested that both the RAG-PCC and XLF ensure stabilization of DNA ends after DNA cleavage by RAG. 24 To further understand the function of XLF during V(D)J recombination and NHEJ, the characteristics of the immunoglobulin heavy chain (IgH), Igk (IgK), Igl (IgL), TR b (TRB), and TR d (TRD) gene rearrangements were studied in 6 XLF-deficient patients, using nextgeneration sequencing.…”
Section: Introductionmentioning
confidence: 99%